Human toxocariosis: a public health problem? - Huapaya H, Pedro (2009)
A bibliographic review was done to update and systematize information on Toxocara human infection. Transmission mechanisms, epidemiology, clinical forms, diagnostic methods and treatment are described. Its importance as an infectious cause of blindness in young people that is potentially preventible and curable by early diagnosis is emphasized. Proposal is done to establish epidemiological surveillance, improve current laws to reduce transmission risk to the general population and increase knowledge on this infection in Peru.